So good : 100 recipes from my kitchen to yours - Blais, Richard, 1972-; Goodbody, Mary (Houghton Mifflin Harcourt, 2017)
The television personality and restaurateur presents recipes that he cooks in his own kitchen, including rabbit au vin, triple-cooked fries, and marshmallow ice cream.